A Two Competing Substrates Michaelis–Menten Kinetics Scheme for the Analysis of In Vitro Starch Digestograms. (1st January 2020) - Meraz, Monica; Alvarez‐Ramirez, Jose; Vernon‐Carter, E. Jaime; Reyes, Isabel; Hernandez‐Jaimes, Carmen; Martinez‐Martinez, Filiberto
Abstract: Progress curves of enzymatic hydrolysis are commonly used for gaining insights on the structure and functionality of native and modified starch. Commonly, heuristic models (e.g., first‐order kinetics) are used to fit the experimental data. Models derived from kinetics schemes provide valuable insights on the digestibility properties of starch. In this work, a two competing substrates Michaelis–Menten scheme with enzyme inhibition by‐products is used for developing a structured model for enzymatic hydrolysis of starch dispersions. The resulting nonlinear model can provide estimates of the hydrolysis dynamics of rapidly and slowly digested starch fractions. The estimation of parameters is carried out by the numerical solution of a least‐squares problem, and illustrated with the hydrolysis by α‐amylase of gelatinized corn starch dispersions. Abstract : Amylolysis of starch dispersions can be described by Monod kinetics. Inhibition of α‐amylase by glucose must be considered in the kinetics scheme. A two‐competing substrate mathematical model describes well experimental data.